The Role of Adaptive Ability in Firm Performance: Moderating Effect of Firm Size and Age - Ngatno; Dewi, Reni Shinta (Asian Economic and Financial Review, 2019)
This paper explores the relationship between adaptive capability and firm performance to determine if corporate managers’ adaptive capabilities could directly impact firm performances. The proposed conceptual model was tested with the moderating effects of firm size and age. An empirical study tested the conceptual model of a batik-industry sample of Indonesian MSMEs. The author used the Generalized Structured Component Analysis (GeSCA) online software program. Empirical findings revealed that adaptive capability could have a positive and significant effect on business performances. These positive relationships tend to decrease when the corporate size is large and have existed for a long period of time. Managers therefore must realize that adaptive capability is needed to improve business performance. It should also be noted that the size of the firm and the age of the firm can reduce the relationship between the two variables.